Hexaethyltripyrrindione (H3Et6tpd): A Non‐Innocent Ligand Forming Stable Radical Complexes with Divalent Transition‐Metal Ions. Issue 29 (7th September 2016) - Bahnmüller, Stefanie; Plotzitzka, Jacqueline; Baabe, Dirk; Cordes, Birte; Menzel, Dirk; Schartz, Katharina; Schweyen, Peter; Wicht, Richard; Bröring, Martin
Abstract : Nickel, palladium, and copper complexes of the tripyrrolic ligand hexaethyltripyrrindione (H3 Et6 tpd, 1 ) have been prepared and characterized by UV/Vis and EPR spectroscopy, as well as by single‐crystal X‐ray structure determination. In all cases the metal ion is coordinated in a distorted square‐planar geometry carrying a water ligand at the fourth coordination site. The Et6 tpd ligand acts as a radical dianion in all cases. In solution, monomeric species are present in which the open‐shell character of the ligand becomes apparent through EPR spectroscopic measurements. In the solid state, the compounds form polymorphs with tightly bonded π–π dimers and chains showing small interplanar distances of 3.191–3.493 Å to one or more neighboring molecules. Magnetic measurements on the complexes confirmed the radical character of the tripyrrindione ligand and revealed strong intermolecular magnetic interactions in these complexes. Abstract : Radical dianionic is the best electronic description of biomimetic tripyrrindione ligands in the ground state of their complexes with divalent ions of nickel, copper, and palladium. The ligand acquires radical character directly upon aerobic metalation and is reminiscent of the antioxidant role of biological tripyrrindiones (the so‐called biopyrrins, e.g., uroerythrin) in living systems.